Penguatan Sektor Mikro terhadap Pembiayaan Al-Qardh Al-Hasan di Bank Syariah Mandiri Cabang Lombok Timur - Baiq Isniarti (ISLAMIKA, 2021)
Referring to the economy of West Nusa Tenggara Province, East Lombok Regency is an area that is considered very suitable for the development of UMKM. There are several reasons that can be put forward, including the very weak economic condition of the community and the very dense population growth according to the community to find their own business to fulfill their daily needs. With this situation, UMKM based businesses have more potential than industrial-based economic business activities. In addition, the socio-religious factors of the community, the majority of which are Muslim, are 90%, as well as the large number of religious educational institutions such as Islamic boarding schools and madrasas that create religious emotional closeness so that they can use Islamic bank products, particularly al-Qardh al-Hasan financing for the development of small and micro businesses. The author can formulate the problem in this study as follows: a) How is the implementation of al-Qardh al-Hasan financing at PT. East Lombok Branch of Bank Syariah Mandiri for UMKM?, b) How is the contribution of al-Qardh al-Hasan financing to the strengthening of Micro Enterprises in East Lombok Regency? This research is a field research, The nature of descriptive research. The implementation of Qardhul Hasan financing at Bank Syariah Mandiri East Lombok Branch is applied in a program called the Umat Partner Program namely: Community Education Program (Economic Empowerment) and Sympathy People (Social Concern), in its development includes productive and consumptive economic activities, social community including education, health. Broadly speaking, this program is divided into economic empowerment activities (manifested in the form of providing Qardhul Hasan loans in the form of business or investment and consumptive capital) and social activities (donations). In the process of implementing this financing, Bank Syariah Mandiri East Lombok Branch provides many conveniences, especially in the process of submitting and paying installments, so that customers feel comfortable with this financing service. And the contribution of Qardhul Hasan funds for micro-businesses customers is an increase in income which is an average of Rp. 400,000, - or about 66%. This increase in income has an effect on the increase in net income (after installments deducted) for customers who previously only earned an average income of Rp. 505,000, - to an average of Rp. 775,000, - per month. With an increase in operating income by 66%, it means that Qardhul Hasan financing has contributed Rp. 235,000, - or 18% for the poor to be above the poverty line.